Assessing stakeholder agreements: a new research focus for CIFOR's plantation programme in Southeast Asia - Guizol, P.; Cossalter, C. (Forest Management Bureau, Department of Environment and Natural Resources, 2001)
The total amount of industrial plantations around the world is still small compared with the total are of global forests, but plantation forestry in the tropics is expected to increase quickly because of growing demand for timber and the depletion of wood from natural forests. Forestry plantations in the tropics have a comparative advantage over temperate plantations in terms of potentially higher yields. Tropical countries are trying to encourage greater private-sector investment in forestry plantations and downstream wood industries. In many countries, however, land ownership and access is disputed by a variety of stakeholders. A major challenge for plantation companies is to reach agreements with these stakeholders to ensure a supply of raw material. Agreements between plantation companies and communities or other stakeholders offer a means of meeting the different objectives of various groups. Yet, in actual forest planning decisions, some stakeholders have more power than the others. This is especially true when large international companies are dealing with local communities whose residents may have little understanding of what an agreement entails. In such a context whether agreements are sustainable is questionable. CIFOR's Plantation Programme is engaged in research to develop tools and methods for assessing and monitoring the viability of such agreements between plantation companies and other stakeholders.